1994
DOI: 10.1095/biolreprod50.3.593
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Rat Epididymal Sperm Immunogenicity by a Seminal Vesicle Secretory Protein and Transglutaminase Both in Vivo and in Vitro1

Abstract: The pretreatment of epididymal spermatozoa with SV-IV, one of the major secretory protein produced by the epithelium of adult rat seminal vesicles, was found to markedly decrease their ability to induce in vivo peritoneal macrophage activation, measured as class II major histocompatibility complex surface antigen expression, superoxide anion production, phagocytic activity, and antigen presentation. In addition, the treatment of spermatozoa with SV-IV produced a significant decrease of their immunogenicity eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 38 publications
7
49
0
Order By: Relevance
“…These data confirm the immunosuppressive activity of SV-IV previously observed in other experimental settings (Paonessa et al, 1984;Metafora et al, 1989;Peluso et al, 1994;Romano-Carratelli et al, 1995;RomanoCarratelli et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These data confirm the immunosuppressive activity of SV-IV previously observed in other experimental settings (Paonessa et al, 1984;Metafora et al, 1989;Peluso et al, 1994;Romano-Carratelli et al, 1995;RomanoCarratelli et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…SV-IV possesses a nonspecies-specific ability to modulate inflammation and humoral and cellmediated immune response (Metafora et al, 1989;Peluso et al, 1994;Romano-Carratelli et al, 1995;Tufano et al, 1996;Santagada et al, 2002), to stimulate horseradish and Se-dependent peroxidases (Metafora et al, 2001 and unpublished data), to protect its target cells against oxidative stress-associated apoptosis and, in particular, to defend nonself epididymal spermatozoa from immunological or reactive oxygen species (ROS) attacks in the female genital tract (Paonessa et al, 1984;Morelli et al, 2007). The anti-inflammatory properties are related to phospholipase A 2 (PLA 2 ) inhibition (Metafora et al, 1989), whereas the pro-inflammatory features are based on SV-IV ability to stimulate mast-cell and basophil degranulation with concurrent release of histamine and other mediators (Metafora et al, manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was reported that rat epididymal sperm immunogenicity could be suppressed by transglutaminase both in vivo and in vitro. The suppression of the epididymal sperm immunogenicity is suggested to be of crucial importance to prevent the immune response when the sperm is introduced into the immunocompetent female genital tract during coitus [21].…”
Section: Discussionmentioning
confidence: 99%
“…), in human seminal fluid and SV secretion (Abrescia, 1985(Abrescia, , 1986Metafora, 1987a). SV-IV possesses potent non-species specific immunomodulatory and antiinflammatory activities, and modulates the coagulation process by affecting the thrombin-antithrombin III (AT) interaction (Galdiero, 1989;Metafora, 1989a, b;Camussi, 1990;Romano-Carratelli 1993;Vuotto, 1993;Di Micco 1994, 2000Peluso, 1994;Mancuso, 1996;Tufano, 1996). Moreover, it can bind the plasma membrane of epididymal spermatozoa, decreasing the immunogenicity of SV-IV (Pavonessa, 1984;Metafora, 1987b;Peluso, 1994).…”
Section: Introductionmentioning
confidence: 99%